Therapeutic Effect of Novel Single-Stranded RNAi Agent Targeting Periostin in Eyes with Retinal Neovascularization - Takahito Nakama; Shigeo Yoshida; Keijiro Ishikawa; Yuki Kubo; Yoshiyuki Kobayashi; Yedi Zhou; Shintaro Nakao; Toshio Hisatomi; Yasuhiro Ikeda; Kazumasa Takao; Kazunori Yoshikawa; Akira Matsuda; et al. (Elsevier, 2017)
Retinal neovascularization (NV) due to retinal ischemia remains one of the principal causes of vision impairment in patients with ischemic retinal diseases. We recently reported that periostin (POSTN) may play a role in the development of preretinal fibrovascular membranes, but its role in retinal NV has not been determined. The purpose of this study was to examine the expression of POSTN in the ischemic retinas of a mouse model of oxygen-induced retinal NV. We also studied the function of POSTN on retinal NV using Postn KO mice and human retinal endothelial cells (HRECs) in culture. In addition, we used a novel RNAi agent, NK0144, which targets POSTN to determine its effect on the development of retinal NV. Our results showed that the expression of POSTN was increased in the vascular endothelial cells, pericytes, and M2 macrophages in ischemic retinas. POSTN promoted the ischemia-induced retinal NV by Akt phosphorylation through integrin αvβ3. NK0144 had a greater inhibitory effect than canonical double-stranded siRNA on preretinal pathological NV in vivo and in vitro. These findings suggest a causal relationship between POSTN and retinal NV, and indicate a potential therapeutic role of intravitreal injection of NK0144 for retinal neovascular diseases. Keywords: periostin, RNAi, neovascularization, diabetic retinopathy